Determination of COVID-19 Vaccine Uptake among People with Underlying Chronic Conditions: A Collaborative Community Approach Study - Bulusu , Aiswarya; Segarra , Cesar; Khayat , Lujain (Advanced Concepts in Medicine and Medical Research Vol. 3, 2023)
The purpose of this chapter is to understand the reason why people choose not to get vaccinated to direct our efforts on health education, health promotion, and to expand our efforts of Community Outreach to the specific population. COVID-19 vaccination has substantially altered the course of the pandemic, saving tens of millions of lives globally. However, inadequate access to vaccines in low-income countries has limited the impact in these settings, reinforcing the need for global vaccine equity and coverage. Understanding the global impact of vaccination on the course of the COVID-19 pandemic is challenging given the heterogeneous access to vaccines coupled with different levels of transmission and ongoing non-pharmaceutical interventions across countries. We conducted an external independent pilot study which would serve as a reliable basis for future studies since the COVID-19 pandemic has proven to be extremely challenging with a constantly mutating virus resulting in continual changes to vaccine mandates, requirement of additional booster doses, and varied perceptions towards the vaccinations. To identify the variables influencing vaccination acceptance across diverse demographics, multivariable regression analyses were carried out. This study explored the acceptance of the COVID-19 vaccination across the wards in DC and how it varies in people with different SDoH and underlying chronic conditions. The current study revealed that people who had no chronic conditions were more likely to get vaccinated when compared to those with one or more than one chronic condition. The importance of this study for public health is that it helps us identify the causes of vaccine hesitancy, which will help us establish trust, expand our reach, provide specialized health education, and improve immunization availability for all populations in the District of Columbia.